2022
DOI: 10.1371/journal.pone.0269854
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of avian hepatitis E virus (Orthohepevirus B) in chickens, ducks, geese, and western capercaillies in Poland

Abstract: Orthohepevirus B, commonly known as avian hepatitis E virus (aHEV), causes big liver and spleen disease (BLS) or hepatitis-splenomegaly syndrome (HSS) in chickens. BLS is an emerging disease among chicken flocks in several countries around the world. In our previous studies, serology and molecular biology screening revealed that chicken flocks are widely affected by aHEV in Poland. The present study, which was conducted between 2019 and 2020, aimed to investigate the prevalence of aHEV in chicken flocks and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Nevertheless, this is the first time that aHEV is reported in common pheasants ( Phasianus colchicus ), extending its natural host range. Such finding, however, is not unexpected as in the last 6 years different studies identified aHEVs in birds other than chickens, demonstrating a much broader natural host range for aHEV than previously considered 10 , 11 , 29 , 30 .…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Nevertheless, this is the first time that aHEV is reported in common pheasants ( Phasianus colchicus ), extending its natural host range. Such finding, however, is not unexpected as in the last 6 years different studies identified aHEVs in birds other than chickens, demonstrating a much broader natural host range for aHEV than previously considered 10 , 11 , 29 , 30 .…”
Section: Discussionmentioning
confidence: 62%
“…Previously, aHEV genotypes 2, 3, and 4 were identified in birds in Poland, revealing that aHEV is widely spread in Polish chicken flocks 11 , 31 33 . Interestingly, some aHEV partial helicase sequences recently reported from broilers and laying hens in Poland, which were assigned to genotype 4 11 , seem to be phylogenetically related to the aHEV genomes reported in the present study. Applying the BLAST search algorithm with newly identified genomes, recognized the above-mentioned genotype 4 isolates as sequences with high nucleotide identity (98.2–99.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatitis E is a disease caused by hepatitis E virus (HEV) (1). HEV is a widespread pathogen found in wild animals (boar, deer) (2,3), domestic pigs (4,5), rats (6,7), chickens (8,9), and humans (10,11). The disease in humans is mostly defined as self-limiting but can be lethal in people with underlying health conditions (12,13), immunosuppressed (14,15), and during pregnancy (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%